Benefits of subsidies to farms that have delivered fruit for processing - Viorica Gavrilă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The objectives of subsidies for agriculture target economic, social and environmental aspects, and the value added from processing contribute to food security and income gaining, being an important method to improve livelihoods. This paper aims to identify the progress made in the fruit sector as a result of financial support through various subsidizing forms, mainly through coupled support for fruit for processing. Having in view the fact that the structure of fruit plantations in Romania reveals that more than half are aged plantations, under decline, with low productive potential, and fruit processing is at a low level, it is necessary to continue to support production intended for processing, possibly with more substantial amounts, to compensate the losses caused by the quality of fruit from less productive plantations and to boost the fruit processing sector.
Keywords: Q12; Q18; 330; farms; fruits; processing